Management of acute submacular hemorrhage using intravitreal injection of tissue plasminogen activator and gas: A case series. (November 2020) - Karamitsos, Athanasios; Papastavrou, Vasileios; Ivanova, Tsveta; Cottrell, David; Stannard, Kevin; Karachrysafi, Sofia; Cheristanidis, Stavros; Ziakas, Nikolaos; Papamitsou, Theodora; Hillier, Roxane
The objective of this case series is the evaluation of the efficacy and visual outcomes after displacement of subretinal hemorrhage using intravitreal injection of recombinant tissue plasminogen activator, expansile gas, and in some cases an anti-vascular endothelial growth factor agent. A case series of 28 eyes of 28 patients (16 men and 12 women with age range 67–95 years) suffering from subretinal hemorrhage (duration range 1–15 days) caused by age-related macular degeneration or retinal macroaneurysm is presented. All the patients were treated with intravitreal injection of recombinant tissue plasminogen activator and gas and some of them received an anti-vascular endothelial growth factor agent between January 2013 and December 2016. The outcomes assessed were visual acuity (preoperatively 1 week, and 1 month postoperatively) with respect to duration and dimension of hemorrhage, displacement of hemorrhage, and possible complications of the procedure. Successful displacement of hemorrhage was achieved in 25 patients (89.3%), 18 of 28 patients had significant improvement in visual acuity 1 week after the treatment, and 22 of 28 patients had significant improvement in visual acuity 1 month after the treatment. The mean improvement of all patients with anatomical displacement of the hemorrhage in visual acuity was 0.7 ± 0.5 (LogMAR) in 1 month. Two patients developed vitreous hemorrhage after the procedure and one retinal detachment. Visual outcome a month after therapy displayed week correlation with duration, diameter, and thickness of hemorrhage. The results lead to the conclusion that intravitreal treatment of recombinant tissue plasminogen activator and expansible gas with or without injection of anti-vascular endothelial growth factor agent is effective in improving visual acuity and displacing submacular hemorrhage secondary to age-related macular degeneration and retinal macroaneurysm. The best functional outcomes can be expected in patients regardless of the size and duration of the hemorrhage.